Tinjauan Terhadap Rekrutmen Dan Pengembangan Perawat Serta Optimalisasi Sumber Daya Manusia Di Rumah Sakit Hermina Arcamanik - Mastin, Mastin; Ariyani, Nurul Dwi (Barongko: Jurnal Ilmu Kesehatan, 2024)
Human resources, especially nurses, are important assets for hospitals in providing quality health services. This study aims to review the recruitment and development process of nurses and to examine the optimization of HR management at Hermina Arcamanik Hospital. The methodology used is a qualitative approach with an interview method. The results of the study indicate that the nurse recruitment process is carried out through administrative selection, written tests, interviews, and health tests. There are obstacles in (1) getting applicants who meet the qualifications. Nurse development is carried out through orientation programs, training, and seminars, but (2) is still limited in scope and budget. In HR management, problems were found related to (3) uneven workload, (4) less conducive work environment, (4) low employee performance and (5) employee health and welfare. Based on the problems above, the researcher provides the following suggestions: (1) Developing a more innovative and adaptive recruitment strategy to attract quality nurses (2) Improving continuous development and mentorship programs to support nurse career development (3) Optimizing workload management and employee welfare programs to improve retention and quality of life.